Предмет: Алгебра,
автор: Podorojnik
x^3-7x-6=0
Помогите пожалуйста
Ответы
Автор ответа:
0
Если x = -1 то -1+7-6=0, верно
Делим выражение на x+1
(x+1)(x²-x-6)=0
D=1+24=25
x = (1+5)/2=3; x = (1-5)/2 = -2.
Ответ:-2,-1,3
Делим выражение на x+1
(x+1)(x²-x-6)=0
D=1+24=25
x = (1+5)/2=3; x = (1-5)/2 = -2.
Ответ:-2,-1,3
Автор ответа:
0
Спасибо,выручил)))
Автор ответа:
0
Пожалуйста)
Похожие вопросы
Предмет: Қазақ тiлi,
автор: orazbekovanurila9
Предмет: Математика,
автор: bralre345621
Предмет: Математика,
автор: davidshmavonyan3
Предмет: Математика,
автор: Аноним
Предмет: Химия,
автор: valtos19